Eksperimen Pembelajaran Matematika Dengan Strategi Kooperatif Tipe Numbered Heads Together Dan Think Pair Share Terhadap Hasil Belajar Matematika Ditinjau Dari Adversity Quotient Siswa Kelas VIII DI SMP Negeri 2 Sukoharjo - MURYANTI, MURYANTI, Prof. Dr. Abdul Ngalim, M.M.,M.Hum (2016)
ABSTRACT The purpose of this research to knows the effect of learning strategies on mathematics learning outcomes in terms from students Adversity Qoutient (AQ). Learning strategies that compared are Numbered Heads Together (NHT) cooperative learning strategy, Think Pair Share (TPS) cooperative learning strategies, and expository learning strategy. This research is appearance experiment. The population for this experiment is all of students in class VIII of junior high school 2 Sukoharjo. The sampling to do with random sampling technique. There are 95 students sample, 31 students in the first grup experiment, 32 students in the second grup experiment, 31 students in control grup. The instruments of this research are mathematich leraning result and AQ quistionnaire. Hypothesis testing use two ways variation analysis with seltaksama. Based on this research, procurable conclusion as follows. 1) NHT type of cooperative learning strategy gives better mathemathics learning results than TPS cooperative learning strategy and expository learning. TPS cooperative learning strategy gives better result than expository learning strategy in flat side geometry. 2) Students with climbers category have better mathemathics learning result than students with campers and quitters category. Students with quitters campers category have better mathemathics learning result than students with quitters category. 3) There are no interaction betwen lerarning strategy and AQ of students about learning results. It shows that learning strategy has no efffect about AQ category. Key Words : NHT, TPS, expository, Adversity Quetient.